NanoScience in Biomedicine - Shi, Donglu. (Springer Berlin Heidelberg, 2009)
NanoScience in Biomedicine provides up-to-date information in the frontier fields of nano biomedicine focusing on basic concepts and recent developments in many topical areas including particular nanomaterials synthesis, field emission of carbon nanotubes, flexible dye-sensitized nano-porous films, magnetic nanofluids, and intrinsically electroconducting nanoparticles. Novel methods of synthesizing nanoscale biomaterials and their applications in biomedicine are also included such as nano-sized materials for drug delivery, bioactive molecules for regenerative medicine, nanoscale mechanisms for assembly of biomaterials, and nanostructured materials constructed from polypeptides. This book is organized in three parts: Part I introduces most recent developments in all aspects of design, synthesis, properties, and applications of nanoscale biomaterials. Part II focuses on novel nanotechnologies in biomedicine. Part III includes some of the new developments of nanomaterials synthesis and recent studies on nanostructure-properties relationships. The book comprehensively addresses the most critical issues in a tutorial manner so that technical non-specialists and students in both biomedical sciences and engineering will be able to benefit. All chapters are contributed by internationally recognized scholars. Dr. Donglu Shi is a professor at the Chemical and Materials Engineering Department, University of Cincinnati, USA.